2005
DOI: 10.1038/sj.onc.1208892
|View full text |Cite
|
Sign up to set email alerts
|

NRG1 gene rearrangements in clinical breast cancer: identification of an adjacent novel amplicon associated with poor prognosis

Abstract: Rearrangements of the neuregulin (NRG1) gene have been implicated in breast carcinoma oncogenesis. To determine the frequency and clinical significance of NRG1 aberrations in clinical breast tumors, a breast cancer tissue microarray was screened for NRG1 aberrations by fluorescent in situ hybridization (FISH) using a two-color split-apart probe combination flanking the NRG1 gene. Rearrangements of NRG1 were identified in 17/382 cases by FISH, and bacterial artificial chromosome array comparative genomic hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 35 publications
7
82
2
Order By: Relevance
“…The group of breaks at NRG1 and possible cluster of breaks 5 0 of UNC5D are indicated. The most frequent core amplicon (defined previously, Garcia et al, 2005;Prentice et al, 2005) includes ZNF703, previously named FLJ14299, and may extend to RAB11FIP1. The inversion and deletion accompanying the translocation in T-47D illustrates that the distal break may not be the rearrangement that is selected for.…”
Section: Is There a Tumour Suppressor?mentioning
confidence: 99%
See 4 more Smart Citations
“…The group of breaks at NRG1 and possible cluster of breaks 5 0 of UNC5D are indicated. The most frequent core amplicon (defined previously, Garcia et al, 2005;Prentice et al, 2005) includes ZNF703, previously named FLJ14299, and may extend to RAB11FIP1. The inversion and deletion accompanying the translocation in T-47D illustrates that the distal break may not be the rearrangement that is selected for.…”
Section: Is There a Tumour Suppressor?mentioning
confidence: 99%
“…FGFR1, at 38.4 Mb, although originally proposed as the principle target for amplification in this region, is not included (Ray et al, 2004;Garcia et al, 2005;Prentice et al, 2005). This amplicon we defined using the same array on breast tumour tissues (Garcia et al, 2005), and it was independently identified by Prentice et al (2005).…”
Section: Amplificationsmentioning
confidence: 99%
See 3 more Smart Citations